Gender and genre: the empirical recognition of “conversational narrator” in women’s fiction (Comparatismi, 2025)
This article examines the interplay between gender and narrative form, with particular attention to the identification and function of the conversational narrator in women’s writing. Drawing on the experimental paradigm developed by Bortolussi and Dixon, this article reports the findings of two exploratory empirical studies designed to assess how selected narrative features influence the perception of a female conversational narrator. Employing a mixed between- and within-subjects experimental design, participants read literary excerpts manipulated along two principal dimensions: linguistic gender markers and narrative perspective. Measures included author recognition, narrative transportation, and message evaluation. The results contribute to a more precise understanding of the narrative strategies and compositional conventions associated with the macro-genre of women’s fiction.
Keywords: Gender; Genre; Conversational narrator; Focalization; Women’s literature